Implementasi e-Modul Pembelajaran pada MatImplementasi e-Modul Pembelajaran pada Mata Kuliah Strategi dan Metode Pembelajaran untuk Mendukung Pembelajarana Kuliah Strategi dan Metode Pembelajaran untuk Mendukung Pembelajaran Aktif Mahasiswa di Era Digital - Agussalim, Hastuti; Nur, Andi Bulqiah; Afni, Nur; Almur, Faathir; Faika, Sitti (MAMMIRI: JURNAL PENGABDIAN MASYARAKAT, 2024)
Digital transformation requires universities to provide learning media that support the needs of today's generation of students. This community service activity aims to improve the quality of active student learning through the implementation of e-modules in the Learning Strategy and Methods course in the Chemistry Education Study Program, Makassar State University. This activity involves the design stage, e-module creation, limited readability test, and socialization. The results of the readability test show that this e-module is very practical, with an acceptance rate of 81.55%. This e-module is considered to support interactive learning. This activity concludes that e-modules are an effective medium to support active learning in the digital era, with recommendations for increasing digital literacy for students and lecturers.